Outdoor-indoor corrosion of AISI 1010 steel in UMP Pekan - Mong, Bee Tong (2012)
This project intends to study the outdoor and indoor atmospheric corrosion behavior of AISI 1010 steel over time of exposure in University Malaysia Pahang, Pekan. The project is an experimental analysis in which exposure tests were carried out in accordance to ASTM G1 and ASTM G50. The AISI 1010 steel were exposed for a total of 6 weeks from 1st March 2012 to 12th April 2012. In order to determine and evaluate the atmosphere characteristics, the atmospheric temperature, dew point temperature and relative humidity were monitored. The corrosion products were observed by visually and SEM analysis. It is found that the lepidocrocite and geothite are the major constituents of the corrosion product. Furthermore, the corrosion rate was obtained from the mass loss by applying the equation accordance to ASTM G50. It is noted that the mass loss of both indoor and outdoor atmosphere is increased but tended to stabilize over exposure time. However, the corrosion rate of the outdoor atmosphere is found higher compared to indoor exposure. As a result, the corrosion rate of AISI 1010 steel which exposed at University Malaysia Pahang, Pekan depends mainly on the type of atmospheres rather than time of exposure.